Reflective practice and self-reliance development among nursing students:What contribution to academic success? - Zineb El Atmani; El Mehdi Bellfkih; Mourad Madrane (Cakrawala Pendidikan: Jurnal Ilmiah Pendidikan)
This study examines the importance of reflective practice (RP) in nursing education and its impact on the development of autonomy and academic success among nursing students. A validated questionnaire was distributed through the Google Forms platform to 200 nursing students from 21 Higher Institutes of Nursing Professions and Health Technologies (ISPITS) across Morocco. The study has both descriptive and exploratory objectives, seeking to understand the level of RP development in Moroccan ISPITS, its relationship with the development of autonomy among nursing students, and its impact on their academic success. The results of this study indicate that RP is an essential component of nursing education, with a positive impact on the development of autonomy and academic success among nursing students. Statistical tests confirm the significance of RP training in ISPITS, suggesting that the promotion of reflective practice in nursing education is an effective means of enhancing the quality of patient care and improving overall healthcare outcomes. This study emphasizes the need for further research on RP and its relationship with nursing education in different contexts and regions to enhance the quality of healthcare services globally. Overall, the study highlights the importance of RP development in nursing education and its positive impact on nursing students' professional growth and academic success.